Resurfacing of facial acne scars with pulsed carbon dioxide laser: a case series of 10 patients - Gosavi, Anil P.; Chavan, Ravindranath B.; Kundale, Darshana R.; Bhatt, Neelam (International Journal of Research in Dermatology, 2020)
Acne vulgaris is a common skin disorder affecting 80% of people between 11-30 years of age with many experiencing some degree of scarring. Pulsed wave carbon dioxide (CO2) laser resurfacing is a recent addition in armamentarium of treatment options for acne scars. This study focuses on one of the most common type of acne complication - atrophic scars treated with pulsed wave carbon dioxide laser. To evaluate efficacy of pulsed carbon dioxide laser for treatment of mild to moderate atrophic facial acne scars. 10 subjects (6 male and 4 females, aged 22-35 years) with skin type III-V and atrophic acne scars were treated with 4 sessions of carbon dioxide non-ablative laser resurfacing on 6 weeks interval. 7 out of 10 subjects in our study perceived an excellent to good improvement with 2 patients showing fair improvement and 1 patient with no improvement. Adverse effects were limited to prolonged erythema (two patients), and post-inflammatory hyperpigmentation (three patient). Excellent to good clinical improvement observed in 70% of patients with acne scars. This underscore pulsed carbon dioxide laser’s effectiveness in the treatment of mild to moderate atrophic acne scars.